Effects of extremely low frequency pulsed electromagnetic field added to kinesitherapy procedure on quality of life in patients with end stage renal disease on dialysis - Rakočević-Hrnjak, Aleksandra; Vuksanović, Miljanka; Dimković, Nada; Djurović, Aleksandar; Petronijević, Nataša; Petronijević, Milan (Vojnosanitetski pregled, 2020)
Abstract Introduction. Extreme Low Frequency Pulsed Electromagnetic Magnetic Field (ELF-PEMF) has a wide range of therapeutic applications which has expanded during the last decades. ELF-PEMF as non-invasive, long term safe method of physical therapy can influence a variety of aspects in chronic diseases including quality of life. Patients with chronic kidney disease (CKD) especially with end stage renal disease (ESRD) treated by dialysis have lower health-related quality of life and changed normal way of living because of ESRD-related co morbid illnesses, associated conditions and complex dyalisis procedures. The objective of this study was to assess the effectiveness of long-term ELF-PEMF in concordance with exercising on the quality of life in ESRD patients on dialysis. Methods. Total of 151 patients with ESRD on dialysis program were subjected on voluntary basis to the treatment with ELF-PEMF (18 Hz, 2 mT) applied during 40 minutes after ten consecutive dialysis procedures, four times through one year (120 treatments in total during three years) together with kinesitherapy (study group) or only to kinesitherapy (control group). The quality of life was assessed through SF36v2 and FACIT Fatigue v4 questionnaires. Results. After the three-year prospective clinical trial 124 patients have completed the study. In study group (n=54), treatment with ELF-PEMF significantly improved FACIT Fatigue v4 scale score as well as physical health, physical functioning, bodily pain and energy/fatigue domains of SF=36v2 scale. There were no effects on mental health domain, limitations due to physical health problems, limitations due to personal or emotional problems, emotional well-being, social functioning, and general health perceptions. In the control group (n=70), no beneficial effects on FACIT Fatigue v4 scale and SF36v2 scale item were noticed. Conclusion. ELF-PEMF could be a additional and safe strategy for improving the quality of life in patients with ESRD on dialysis.